EVALUASI KINERJA JARINGAN WIFI DI SMKN MANONJAYA MENGGUNAKAN PARAMETER QUALITY OF SERVICE (QOS - Fatya Lihawa Awaliyah; Dalva Daliah Mutiara Muhibbatul Millah; Helmy Dzulfikar (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
This study aims to evaluate the performance of WiFi networks at SMKN Manonjaya using Quality of Service parameters including throughput, delay, jitter, and packet loss. The research method used is descriptive with a qualitative approach through observation, interviews, documentation, and network testing in several areas such as classrooms, canteens, and laboratories. The measurement results show that network quality is strongly influenced by the level of network usage. In the Ringnet network during break time, throughput is low while delay and jitter are high, whereas during learning activities throughput increases with lower delay and jitter values. Meanwhile, the Aula network shows fairly good throughput but relatively high packet loss. The results indicate that the main factors affecting network quality include the number of users, bandwidth capacity, and distribution of network devices. Therefore, optimization of bandwidth management, addition of access points, and improvement of network monitoring and maintenance are required to achieve a more stable, evenly distributed, and optimal network service to support digital learning activities.